The Role of Bhabinkamtibmas with Personal Smart Tools to Maintain Precision Kamtibmas in the Jurisdiction of The Pekalongan Police Region - Andreas Watratan (Advances in Police Science Research Journal, 2022)
This Final Project is based on the important role of Bhabinkamtibmas in maintaining Precision Kamtibmas. The formulation of the problems discussed in this Final Project is about the condition of Bhabinkamtibmas' role with the application of personal smart tools, the condition of Kamtibmas during the application of personal smart tools and efforts to increase the role of Bhabinkamtibmas by implementing personal smart tools to maintain Kamtibmas. The purpose of writing this Final Project is to find out the correlation of the role of Bhabinkamtibmas with personal smart tools and maintenance of Kamtibmas by discussing in terms of roles, conditions of Kamtibmas and efforts to optimize the role of Bhabinkamtibmas with personal smart tools to maintain precise Kamtibmas in Pekalongan Regency. The research method used is a qualitative research method with data analysis techniques in the form of interviews, Focus Group Discussion (FGD) with various related parties, observations, and document studies with a theoretical approach, namely the role theory of Edi Suhardono and management theory of George R. Terry. The results of this study indicate that in fact the role of Bhabinkamtibmas with personal smart tools has a positive contribution to the maintenance of Kamtibmas although currently, there are still shortcomings in several aspects of management. For this reason, it is necessary to manage aspects of Bhabinkamtibmas personnel, budget, connectivity facilities, in the form of support for communication tools, methods and the community environment so that the role of Bhabinkamtibmas with the application of personal smart tools can increase effectiveness in maintaining Kamtibmas in Pekalongan Regency.